Optimasi mikrobiologik tandan kosong kelapa sawit untuk produksixilosa oleh Aspergillus sp. TnP 32=Optimiza tion of the Microbiologica I Fermentation front the Oil Pa Im Empty Fruit Bunches for ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT The xylose production of the microbiological fermentation was studied from the oil palm empty fruit bunches by Aspergillus sp. The growing of TnP32 in medium containing different nitrogen concentration was studied. The effect a number of environmental parameters (e.g. temperature, pH and time incubation) was also investigated. The concentration of reducing sugar and xylose production were found to vary between different nitrogen concentration. The highest concentration of reducing sugar and xylose production of each experimental were obtained by incubating for 48 h, and after that consisted. The optimum pH for the concentration of reducing sugar and xylose production occurred in the pH range of 5.5 to 6.5